MENTAL STABILITY - WHAT DOES IT MEAN AND HOW TO ACHIEVE IT (GYMNASIUM, 2009)
Talking about mental stability of course focuses on a positive state of mind thus resulting in a goodperformance.The performance of any athlete in this status is very good, sometimes remarkably beyond theirregular capacity.The most recent researches do lead to the level of self value of the respective athlete as the mostdecisive factor of the stabilization of performance.The crucial point is to find certain drills and configurations of tasks that will give a good chance forthe athlete to be successful in showing competence.